Competency, Allotment, and the Canton Asylum: The Case of a Muscogee Woman - Anne Gregory (Disability Studies Quarterly, 2022)
No abstract available.
Keywords: ableism; Canton Asylum; Muscogee (Creek) history; allotment; institutionalization; erasure; settler colonialism; survivance